Evaluation of information sources in marketing : a study of business buyers in Singapore. - Purnima Kamath. (2008)
One of the challenges facing marketing managers in international markets is how best to carry their sales messages to the decision-makers who make the purchase decisions. An excellent product can never be successful in the marketplace if its benefits are not communicated effectively to target consumers. There is an increasing diversity of communication approaches available to marketers to reach their end consumers, channel intermediaries and other constituencies. As a result, the implementation of communication policy promises to be both complex and more challenging.